EFEKTIVITAS PENYULUHAN TENTANG KESEHATAN GIGI DAN MULUT DENGAN METODE CERAMAH DAN DISKUSI KELOMPOK TERHADAP PENGETAHUAN RESPONDEN (STUDI LITERATUR) - Sri Mulyanti; Isa Insanuddin; salsabila apsari; Irwan Supriyanto (Poltekkes Kemenkes Bandung, 2021)
Dental and mouth disease is a disease that can attack all age groups, and has a progressive attitude if not treated or treated which will get worse. Riskesdas (2018) recorded data nationally for the proportion of dental and mouth problems (tooth decay/cavity/pain) of 45.3%, and the highest dental and mouth problems experienced by residents in the age group of 5-9 years which amounted to 67.3 %. This research was conducted with the aim to find out the effectiveness of dental and oral health counseling on respondents’ knowledge by using the lecture method and the group discussion method, namely in September 2019 until May 2020. The research method used is the study of literature by collecting data related to research from literature which is then examined. The data used are secondary data that is data obtained from the results of previous studies or sources of literature and data collection methods used are literature studies, namely by collecting various references about counseling with lecture methods, group discussions and the level of knowledge about oral health. Data analysis method used is the content analysis method or descriptive analysis method which is done by describing the facts obtained and then analyzed. The data obtained is compiled and analyzed so that conclutions can be obtained that can answer the reseach objectives based on the study of literature studies.The results of the literature study show that there are differences in respondents' knowledge after counseling with the lecture method and the group discussion method. The average value of respondents’ knowledge after the counseling intervention with the group discussion method is greater than the lecture method, so it can be concluded that the group discussion method is more effective in increasing respondents' knowledge about oral and dental health than the lecture method. The effectiveness of health education methods is influenced by various factors including responden characteristics such as age, education level, etc. So that it can give different effectiveness results. Key words : lecture, discussion, efffectiveness